Pengaruh Minat Baca Pemuda terhadap Tingkat Perkembangan Intelektual Masyarakat - Gilang Riski (Lifelong Education Journal, 2021)
The purpose of this research is to know the role of youth with their reading interest and the effect that will be given to the people who live around the youth environment. The intellectuality of society is very dependent on the interest of youth to touch their scientific fields so that with a high reading level, they can improve the intellectuality of the community. The approach taken in this research is qualitative and uses descriptive method. Literature study is the data collection technique used in this study. To analyze the data using an interactive model that includes data collection, reduction, presentation and drawing conclusions. After looking at the results of the study, it can be seen that the intellectual level of the community goes hand in hand with the youth's interest in reading. Where youth as agents of change act as the spearhead in updating community knowledge which will continue to change over time. The reading level of youth will contribute to society in the long term and also allow it to become a momentum in growing the intellectuals of the next generation. In their role as spearheads, youth are required to continue to supply the latest knowledge to the surrounding community.